Study of Density of Proton-Rich and Neutron-Rich Bands - Merzaee, Dowood (Journal of Natural Sciences – Kabul University, 2020)
Nuclear level density (NLD) is one of the important properties of nuclei with widespread applications, including astrophysics and nuclear medicine. There has been limited experimental and theoretical research on nuclei that are far from the stability line, making the study of NLD for these nuclei crucial. Additionally, NLD is an essential input for nuclear research codes, and therefore, methods for calculating this parameter are important. In this study, a detailed spectral distribution method was used to determine the density of two neutron-rich and proton-rich magical energy bands with the same mass number.